The importance of programmatic health actions in tuberculosis control: experience of a Primary Health Care Service in Porto Alegre, Rio Grande do Sul, Brazil - Souza, Camila Furtado de; Ben, Ângela Jornada; Schneider, Silvete Maria Brandão; Nascimento, Bianca Peixoto; Neumann, Cristina Rolim; Oliveira, Francisco Jorge Arsego Quadros de (Clinical and Biomedical Research, 2014)
Introduction: Tuberculosis deserves special attention from health professionals and society. However, health services are not organized to attend these patients, and the prevalence of the disease remains high in the country. The objective of this paper is to demonstrate the role of primary care in improving tuberculosis indicators with structured programmatic actions. Methods: Data from patients diagnosed with tuberculosis linked to the Primary Health Care Service of the Hospital de Clínicas de Porto Alegre, attended in the health care services of the city, were analyzed and compared before (2002-2008) and after (2009-2012) the implementation of a Tuberculosis Control Program. The indicators were analyzed based on the goals established by WHO. Results: One hundred and forty patients had tuberculosis between 2002 and 2012, 94 before the implementation of the Program and 46 after. With the Program, the annual number of tracked respiratory symptomatic patients and patients diagnosed with tuberculosis increased. Also, the diagnosis of tuberculosis in primary care services increased from 4.3% (n = 4) to 39.1% (n = 18) (p <0.001); and there was an improvement in cure (78.2% to 85.7%) and therapy dropout (9.3% to 9.1%) rates. Conclusion: Our study showed that, after implementation of the Tuberculosis Control Program in the Primary Health Care Service of the Hospital de Clínicas dePorto Alegre, there was improvement in diagnosis of the disease, cure and treatment dropout rates, which have reached the cure rate goal established by the Ministry of Health.